Recent progress in the structure control of Pd–Ru bimetallic nanomaterials - Wu, Dongshuang (Sci Technol Adv Mater, 2016)
Pd and Ru are two key elements of the platinum-group metals that are invaluable to areas such as catalysis and energy storage/transfer. To maximize the potential of the Pd and Ru elements, significant effort has been devoted to synthesizing Pd–Ru bimetallic materials. However, most of the reports dealing with this subject describe phase-separated structures such as near-surface alloys and physical mixtures of monometallic nanoparticles (NPs). Pd–Ru alloys with homogenous structure and arbitrary metallic ratio are highly desired for basic scientific research and commercial material design. In the past several years, with the development of nanoscience, Pd–Ru bimetallic alloys with different architectures including heterostructure, core-shell structure and solid-solution alloy were successfully synthesized. In particular, we have now reached the stage of being able to obtain Pd–Ru solid-solution alloy NPs over the whole composition range. These Pd–Ru bimetallic alloys are better catalysts than their parent metal NPs in many catalytic reactions, because the electronic structures of Pd and Ru are modified by alloying. In this review, we describe the recent development in the structure control of Pd–Ru bimetallic nanomaterials. Aiming for a better understanding of the synthesis strategies, some fundamental details including fabrication methods and formation mechanisms are discussed. We stress that the modification of electronic structure, originating from different nanoscale geometry and chemical composition, profoundly affects material properties. Finally, we discuss open issues in this field.